2016
DOI: 10.1093/icvts/ivw179
|View full text |Cite
|
Sign up to set email alerts
|

Computational haemodynamic analysis of left pulmonary artery angulation effects on pulmonary blood flow

Abstract: Acute LPA angulation is associated with adverse haemodynamic performance. This should be particularly addressed during the reconstruction of pulmonary artery in the repair of tetralogy of Fallot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…Area obstructions (stenosis) of the proximal PAs, steeper branching angles and curvatures as well as other anatomic alterations can lead to a completely different flow morphology, as shown for instance in the case of TGA patients after the arterial switch operation [6,7]. Zhang et al computationally analyzed the effect of the LPA branching angle (i.e., the angle formed between the MPA and LPA centerlines) and found a dramatic decrease of the energy efficiency with decreasing angles (i.e., sharper bends) [21]. Progresses in SSM methods, such as the one used in this work, are allowing a more quantitative analysis of the correlation between certain shape features and functional indices.…”
Section: Global Flow Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Area obstructions (stenosis) of the proximal PAs, steeper branching angles and curvatures as well as other anatomic alterations can lead to a completely different flow morphology, as shown for instance in the case of TGA patients after the arterial switch operation [6,7]. Zhang et al computationally analyzed the effect of the LPA branching angle (i.e., the angle formed between the MPA and LPA centerlines) and found a dramatic decrease of the energy efficiency with decreasing angles (i.e., sharper bends) [21]. Progresses in SSM methods, such as the one used in this work, are allowing a more quantitative analysis of the correlation between certain shape features and functional indices.…”
Section: Global Flow Featuresmentioning
confidence: 99%
“…Of note, Geiger et al found again right-handed helical flow in the RPA of 8 (out of 12) controls [17]. Other investigations focused on TOF and adverse haemodynamic consequences of post-operative morphology [20][21][22]. Recently, Boumpouli et al analyzed computationally the effect of the branching angle on flow separation in the pulmonary bifurcation, in the context of TOF [23].…”
Section: Introductionmentioning
confidence: 99%
“…By matching closely computational predictions with experimental results, we can develop more complex models of the pulmonary arterial network with the objective of addressing, on a patient-specific basis, the potential role of computational hemodynamics as an aid to right heart catheterization in the diagnosis or follow-up of PH patients. A recent study by Zhang et al 51 reports on the three-dimensional reconstruction of the MPA from patient-specific images and the use of CFD for such reconstructed models. They analyzed the effect of different LPA angulations on the MPA hemodynamics and found that acute angulation of the LPA is associated with adverse hemodynamic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Many of those studies have concentrated mainly on assessment of shear stress (9, 10). Nevertheless, it has been shown that increased energy loss (EL) is closely related to the long-term outcome of patients (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%